0 votes
49 views
in Maths by (30.0k points)

(a) x² + 4=0

(b) x² - 4=0

(c) 4x² - 1=0

(d) x² - 2=0

1 Answer

0 votes
by (237k points)
 
Best answer

Correct option is (b) x² - 4=0

Solution:

Let the roots of a quadratic be α and β

thus the quadratic is x² - (α+β)x + αβ=0

If α=2, and α+β =0

⇒β=-2

thus αβ= 2(-2) = -4

Thus the quadratic equation becomes:

x² - 0x + (-4) =0

⇒ x² -4 =0

Related questions

0 votes
1 answer 54 views
0 votes
1 answer 88 views
0 votes
1 answer 65 views
0 votes
1 answer 78 views
0 votes
1 answer 55 views
...